Postharvest Technology of Button Mushroom: A Socio-Economic Feasibility - Kumar, Santosh; Chand, Gireesh; Srivastava, J N; Ahmad, Md Shamsher (Journal of Postharvest Technology, 2014)
Fresh mushroom is highly perishable and deteriorates  immediately after harvest. It develops brown colour on the  surface of the cap due to the lyses of cell and enzymatic action of  polyphenol oxidase that results in shorter shelf life. Being highly  perishable in nature, the fresh mushrooms need to be processed to  extend the off-season availability by adopting appropriate  postharvest technology and processing into value-added products.  The value-added products are the need of the hour for the  mushroom growers not only to reduce the losses but also to  enhance the income by value-addition to boost the consumption  of mushroom. The possible value-added products can be  developed either by converting freshly harvested mushrooms into  ketch-up, murabba, candy, chipsand pickles or by dehydrating  freshly harvesting mushrooms into dehydrated form and then  making soup powder, biscuit, nuggets and Ready–to–eat  mushroom curry (RTE). This review article summarizes the  information regarding postharvest technologies and value  addition of fresh mushroom generally followed worldwide.
Keywords: Button Mushroom; Physiological changes; Biochemical changes; Packaging; Value added products